Identification of AGO2 and PLEC genes polymorphisms in Hu sheep and their relationship with body size traits - Jia Liu; Wenxin Zheng; Weimin Wang; Xiaobin Yang; Yongliang Huang; Panpan Cui; Zongwu Ma; Xiwen Zeng; Rui Zhai; Xiuxiu Weng; Weiwei Wu; Xiaoxue Zhang (Animal Biotechnology, 2024)
The body size traits are major traits in livestock, which intuitively displays the development of the animal’s bones and muscles. This study used PCR amplification, Sanger sequencing, KASPar genotyping, and quantitative real-time reverse transcription PCR (qRT-PCR) to analyze the Single-nucleotide polymorphism and expression characteristics of Argonaute RISC catalytic component 2 (AGO2) and Plectin (PLEC) genes in Hu sheep. Two intron mutations were found in Hu sheep, which were AGO2 g.51700 A > C and PLEC g.23157 C > T, respectively. Through association analysis of two mutation sites and body size traits, it was found that AGO2 g.51700 A > C mainly affects the chest and cannon circumference of Hu sheep of while PLEC g.23157 C mainly affects body height and body length. The combined genotypes of AGO2 and PLEC genes with body size traits showed SNPs at the AGO2 g.51700 A > C and PLEC g.23157 C > T loci significantly improved the body size traits of Hu sheep. In addition, the AGO2 gene has the highest expression levels in the heart, rumen, and tail fat, and the PLEC gene is highly expressed in the heart. These two loci can provide new research ideas for improving the body size traits of Hu sheep.